Scientists in Lyudmila Ulitskaya’s Novels - Szabó, Tünde (Slavica, 2021)
This study focuses on a characteristic type of hero in Ulitskaya’s works and analyses the image of the scientist heroes and their poetic functions in three of the author’s novels (The Kukotsky Enigma, The Big Green Tent and Jacob’s Ladder). These heroes represent a special kind of syncretic thinking. Firstly, in their conversations and debatesthe genre code of the Socratic dialogue is activated, as Mikhail Bakhtin described it in connection with the development of the polyphonic novel. Secondly, these heroes, who always appear in pairs, invoke the duo of Don Quixote and Sancho Panza, as well as certain characteristics of “Quixotism”, which has a central role in the critique of the role that intellectuals have played in Russian culture. It is against the above background that the role of 20th-century intellectuals gains a new interpretation in Ulitskaya’s three novels.